Targeting ATF6 reduces pathological neovascularization and improves visual outcomes in retinal disease models - Bradley, Allyssa; Park, Soyoung; Park, Soyeon; Kim, Kyle; Galdamez, Angela; Min, Hyejung; Diaz-Aguilar, Monica Sophia; Hartnett, M. Elizabeth; Lee, Eun-Jin; Lin, Jonathan H. (Scientific reports, 2025)
Pathological retinal neovascularization is a cause of vision loss in diseases including retinopathy of prematurity (ROP), wet age-related macular degeneration (AMD), and diabetic retinopathy. The Unfolded Protein Response (UPR) is an intracellular signal transduction mechanism that is activated by ER stress and upregulates many proteins, including angiogenesis factors like VEGF and HIF-1α. This suggests that UPR genes and pathways may drive retinal angiogenesis. Here, we tested the role of the UPR regulator Activating Transcription Factor 6 (ATF6) in pathological and developmental retinal angiogenesis. We induced pathological retinal neovascularization in Atf6 −/− mice using the oxygen-induced retinopathy (OIR) model and found significantly preserved visual function, accompanied by decreased retinal neovascularization, endothelial cell proliferation, and UPR transcriptional program induction. When we chemically blocked ATF6 signaling by intraocular injection of the small molecule Ceapin-A7, we also saw suppressed retinal expression of UPR genes. Additionally, in postnatal day 7 Atf6 −/− mice when the retinal vasculature is developing in response to physiologic intraocular hypoxia, there was a transient but significant defect in pruning and retinal blood vessel extension. Together, our results demonstrate ATF6’s causal role in developmental and pathological retinal angiogenesis and highlight its potential as a therapeutic target to preserve vision in retinal neovascularization diseases.